Inhibition of acinetobacter baumannii biofilm formation by black pepper extract - Rahman, Nafin; Tanni, Rounok Jahan; Reza, Setuli (Brac University, 2024)
This thesis submitted to the Department of Mathematics and Natural Sciences in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2024.